Incessant Boat Mishaps On Nigerian Inland Waterways- Advisory Way Forward Analysis - Olusegun O.A.; Ogola D. B., (Daha International University Academic Journal (DIUAJ), 2023)
The Nigerian inland waterways cannot be said to be safe as a result of incessant boat accidents, especially during the rainy season. The necessity to develop this paper stemmed from avoidable accidents of boats on the Nigerian Inland Waterways. This paper presented the challenges of boat accidents or crashes in Nigeria with a view to providing relevant solutions to the identified problems. Retrieved data from literatures were used to present boat accidents across littoral states in Nigeria. The secondary data collected was upgraded to capture the recent incidents of boat mishaps across all the States involved in Nigeria. Descriptive statistics were used to showcase the percentages of the accidents across the States, and an advisory way forward to cushion the incessant unfortunate incidents was suggested. It is believed that each Nigerian littoral state will be proactive in utilizing the suggested measures to curb the rate of boat and maritime accidents on our inland waterways.
The Nigerian inland waterways cannot be said to be safe as a result of incessant boat accidents, especially during the rainy season. It is believed that each Nigerian littoral state will be proactive in utilizing the suggested measures to curb the rate of boat and maritime accidents on our inland waterways.
Keywords: inland waterways; boat; mishaps; accidents; Nigeria